Clinical utility of TERT promoter mutations and ALK rearrangement in thyroid cancer patients with a high prevalence of the BRAF V600E mutation. Issue 1 (December 2016) - Bae, Ja; Kim, Yourha; Jeon, Sora; Kim, Se; Kim, Tae; Lee, Sohee; Kim, Min-Hee; Lim, Dong; Lee, Youn; Jung, Chan
Abstract Background Mutations in theTERT promoter, ALK rearrangement, and theBRAF V600E mutation are associated with aggressive clinicopathologic features in thyroid cancers. However, little is known about the impact ofTERT promoter mutations andALK rearrangement in thyroid cancer patients with a high prevalence ofBRAF mutations. Methods We performed Sanger sequencing to detectBRA F V600E andTERT promoter mutations and both immunohistochemistry and fluorescence in situ hybridization to identifyALK rearrangement on 243 thyroid cancers. Results TERT promoter mutations were not present in 192 well-differentiated thyroid carcinomas (WDTC) without distant metastasis or in 9 medullary carcinomas. However, the mutations did occur in 40 % (12/30) of WDTC with distant metastasis, 29 % (2/7) of poorly differentiated carcinomas and 60 % (3/5) of anaplastic carcinomas.ALK rearrangement was not present in all thyroid cancers. TheBRAF V600E mutation was more frequently found in WDTC without distant metastasis than in WDTC with distant metastasis (p = 0.007). In the cohort of WDTC with distant metastasis, patients with wild-typeBRAF andTERT promoter had a significantly higher response rate after radioiodine therapy (p = 0.024), whereas theBRAF V600E mutation was significantly correlated with progressive disease (p = 0.025). Conclusions TheTERT promoter mutation is an independent predictor for distant metastasis of WDTC, butALK testing is not useful for clinical decision-making in Korean patients with a high prevalence of theBRAF V600E mutation. Radioiodine therapy for distant metastasis of WDTC is most effective in patients withoutBRAF V600E andTERT promoter mutations.